L’importance et la signification de l’environnement chez de jeunes adultes français - Chantal Royer; Anaïs Py-Cayol (VertigO, 2022)
This article focuses on the relationship to environment in young adults. It aims to better understand how they see the environment, what value and what meanings they attribute to it. The paper is based on data collected in the context of qualitative interviews carried out with young French adults during the winter of 2021. The analyzes show that the environment is important for the young people encountered. Furthermore, they highlight four universes of meanings which are articulated according to a gradation which goes from a basic and individual thought to a reflection which is at the same time more complex and collective: the environment associated with the protection of nature, waste and pollution, environment associated with the world of consumption and, ultimately, the environment seen as a social and political movement. The results contribute to deepening the knowledge of the relationship to the environment among young people and allow us to glimpse avenues for reflection on the development of environmental values.